Social signaling via bioluminescent blinks determines nearest neighbor distance in schools of flashlight fish Anomalops katoptron - Peter Jägers (Nature Portfolio, 2021)
Abstract The schooling flashlight fish Anomalops katoptron can be found at dark nights at the water surface in the Indo-Pacific. Schools are characterized by bioluminescent blink patterns of sub-ocular light organs densely-packed with bioluminescent, symbiotic bacteria. Here we analyzed how blink patterns of A. katoptron are used in social interactions. We demonstrate that isolated specimen of A. katoptron showed a high motivation to align with fixed or moving artificial light organs in an experimental tank. This intraspecific recognition of A. katoptron is mediated by blinking light and not the body shape. In addition, A. katoptron adjusts its blinking frequencies according to the light intensities. LED pulse frequencies determine the swimming speed and the blink frequency response of A. katoptron, which is modified by light organ occlusion and not exposure. In the natural environment A. katoptron is changing its blink frequencies and nearest neighbor distance in a context specific manner. Blink frequencies are also modified by changes in the occlusion time and are increased from day to night and during avoidance behavior, while group cohesion is higher with increasing blink frequencies. Our results suggest that specific blink patterns in schooling flashlight fish A. katoptron define nearest neighbor distance and determine intraspecific communication.